2009
DOI: 10.1007/s00710-009-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

A melt and fluid inclusion assemblage in beryl from pegmatite in the Orlovka amazonite granite, East Transbaikalia, Russia: implications for pegmatite-forming melt systems

Abstract: Beryl crystals from the stockscheider pegmatite in the apical portion of the Li-F granite of the Orlovka Massif in the Khangilay complex, a tantalum deposit, contain an assemblage of melt and fluid inclusions containing two different and mutually immiscible silicate melts, plus an aqueous CO 2 -rich supercritical fluid. Pure H 2 O and CO 2 inclusions are subordinate. Using the terminology of Thomas R, Webster JD, Heinrich W. Contrib Mineral Petrol 139: 394-401 (2000) the melt inclusions can be classified as (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 22 publications
0
12
1
1
Order By: Relevance
“…More recently, there has been increasing Raman evidence for significant HCO 3 − (aq) and CO 3 2− (aq) in fluid inclusions (Fig. 9c) mainly from pegmatites, ore deposits, and high pressure metamorphic rocks (Frezzotti et al, 2011;Hrstka et al, 2011;Thomas et al, , 2009aThomas et al, ,b, 2011aXie et al, 2009). CO 3 2− (aq) concentrations as low as 0.36 wt.% can be measured using a modified technique by Sun and Qin (2011) (R. Thomas, Kolesov and Geiger, 1998;4 Mernagh and Liu, 1991;5 Sendova et al, 2005;6 Palmeri et al, 2009.…”
Section: Analyses Of Solutes: Polyatomic Ions and Moleculesmentioning
confidence: 98%
“…More recently, there has been increasing Raman evidence for significant HCO 3 − (aq) and CO 3 2− (aq) in fluid inclusions (Fig. 9c) mainly from pegmatites, ore deposits, and high pressure metamorphic rocks (Frezzotti et al, 2011;Hrstka et al, 2011;Thomas et al, , 2009aThomas et al, ,b, 2011aXie et al, 2009). CO 3 2− (aq) concentrations as low as 0.36 wt.% can be measured using a modified technique by Sun and Qin (2011) (R. Thomas, Kolesov and Geiger, 1998;4 Mernagh and Liu, 1991;5 Sendova et al, 2005;6 Palmeri et al, 2009.…”
Section: Analyses Of Solutes: Polyatomic Ions and Moleculesmentioning
confidence: 98%
“…For example, CIs were reported by London [3,4] from the Tanco Li-Ta and Afghan gem pegmatites. Subsequently, CIs were also found in the Keketuohai, Kelumute, and Kuwei pegmatites located in Altay, Xinjiang, China [5][6][7], the Jiajika LiBe-Nb-Ta pegmatite deposit, western Sichuan, China [8], the Ehrenfriedersdorf Sn-W pegmatite deposit, Germany [9], the Orlovka amazonite granite, East Transbaikalia, Russia [10], and the Borborema Pegmatite Province, northeastern Brazil [11]. Currently, the origin of CIs is controversial and has resulted in substantially different understandings for the formation mechanisms behind pegmatites [12].…”
Section: Introductionmentioning
confidence: 99%
“…London [13][14][15][16][17] regarded CIs as representative of a flux-rich hydrous melt boundary layer in his constitutional zone refining model. Thomas et al [10,11,[18][19][20] thought that CIs indicated the occurrence of liquid immiscibility in the granitic magma during formation of the pegmatite. Anderson et al [21,22] suggested a secondary origin for CIs due to a reaction between spodumene and an aqueous-carbonic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Phase ratios of melt inclusions in plutonic rocks are particularly difficult to measure by optical microscopy because they commonly occur as small (≤10 mm) masses of fine-grained minerals ± glass. An inability to resolve individual phases may result in a failure to (1) distinguish crystallized melt from trapped solids (Rapien et al 2003), (2) recognize heterogeneous trapping of immiscible phases (i.e., "composite inclusions"; Kamenetsky et al 2002, Thomas et al 2009), and (3) recognize post-entrapment modifications such as necking, and fluid-host back-reactions (Heinrich & Gottschalk 1995, Anderson et al 2001, Danyushevsky et al 2002, Romer et al 2006.…”
mentioning
confidence: 99%
“…inTRODucTiOn Polyphase inclusions, such as crystallized melt inclusions in plutonic rocks, can provide important constraints on the origin, nature and evolution of the magma at the time of entrapment (Roedder 1984, Thomas et al 2009). According to Bodnar & Student (2006), the conditions at the time of entrapment can be determined from a melt-inclusion assemblage (MIA) if the inclusions within that assemblage display consistent phase-relations and are legitimately closed, isochoric systems that entrapped a single homogeneous phase (i.e., Roedder's rules).…”
mentioning
confidence: 99%